1999
DOI: 10.1055/s-2007-1013120
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Cardiovascular Lesions Caused By Systemic Inflammatory Diseases

Abstract: The effect of fibrin glue on inhibition of pericardial adhesions was tested using 26 beagle dogs. Dacron patches were sutured to the heart and tincture of iodine was applied to promote adhesions. Fibrin glue (3 ml) was sprayed over the patches in 15 dogs (test group), and was not separated in the remaining 11 dogs (control group). All animals in the test group had minimal adhesions between the pericardium and the epicardium or patched region, and an accumulation of gelatinous material was found in the subperic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Aspirin may contribute to a decrease in the the inflammatory process as well. • When cardiovascular surgery is necessary, it is crucial to keep in mind the need to reduce inflammation pre-and postoperatively, to reinforce suture lines, and to select operative procedures accordingly [79].…”
Section: Treatmentmentioning
confidence: 99%
“…Aspirin may contribute to a decrease in the the inflammatory process as well. • When cardiovascular surgery is necessary, it is crucial to keep in mind the need to reduce inflammation pre-and postoperatively, to reinforce suture lines, and to select operative procedures accordingly [79].…”
Section: Treatmentmentioning
confidence: 99%
“…9 Thus it is crucial to reduce inflammation preoperatively and postoperatively, to reinforce the suture line, and carefully select the operative procedure for treatment of cardiovascular disorders caused by systemic inflammatory diseases. 10 In a study by Stamp and colleagues 7 of a patient with HLA-B27-associated spondyloarthropathy and severe ascending aortitis, sulfasalazine, prednisolone, cyclophosphamide, or azathioprine treatment was administered preoperatively because of extensive systemic inflammation and rapid expansion of the ascending aortic aneurysm. They focused on reducing potential postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the increased risk of surgical procedures during active disease [1,22,24,27] but Miyata and colleagues showed that systemic inflammation and steroid administration had little influence on formation of anastomotic aneurysm [23]. Instead, anastomotic aneurysm tended to occur after operations for aneurismal lesions.…”
Section: Discussionmentioning
confidence: 99%